Loading

Y = x + 4y = x^{2} + 4x(as both are equal to y, they can be equated)So: x^{2} + 4x = x + 4(Rearrange to make the equation equal 0 - subtract x and 4)x^{2} + 3x - 4 = 0(factorise)(x + 4)(x - 1) = 0Therefore: x = -4 or x = 1(plug these values back into the original equation to find the corresponding values of y)If x = -4, y = - 4 + 4So y = 0If x = 1, y = 1 + 4So y = 5 This means the solutions to these equations are:x = -4 and y = 0x = 1 and y = 5

One to one online tution can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor

One to one online tution can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor